2019
DOI: 10.1002/pbc.27629
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of early cancer surveillance for patients with Li–Fraumeni syndrome

Abstract: Introduction Patients with germline TP53 pathogenic variants (Li–Fraumeni syndrome [LFS]) are at extremely high lifetime risk of developing cancer. Recent data suggest that tumor surveillance for patients with LFS may improve survival through early cancer detection. The objective of this study was to assess the cost‐effectiveness of a cancer surveillance strategy for patients with LFS compared with those whose tumors present clinically. Methods A Markov decision analytic model was developed from a third‐party … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Potential cost savings exist through cancer screening and early detection, prevention, PGT and potentially more effective therapeutics; however, there are also significant costs associated with each of these in addition to the costs of sequencing and clinical genetics visits. Studies of cost-effectiveness in this area to date have focused on individual pieces of this process, for example, cancer screening in patients with LFS 37 . The full analysis of the effects of pan-pediatric cancer germline sequencing will require long-term follow-up, as costs may be largely up front (that is, sequencing), while cost savings may not be realized for many years (that is, through early tumor detection associated with need for less treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Potential cost savings exist through cancer screening and early detection, prevention, PGT and potentially more effective therapeutics; however, there are also significant costs associated with each of these in addition to the costs of sequencing and clinical genetics visits. Studies of cost-effectiveness in this area to date have focused on individual pieces of this process, for example, cancer screening in patients with LFS 37 . The full analysis of the effects of pan-pediatric cancer germline sequencing will require long-term follow-up, as costs may be largely up front (that is, sequencing), while cost savings may not be realized for many years (that is, through early tumor detection associated with need for less treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, 5‐year overall survival was 88.8% (95% CI, 78.7‐100) among those who agreed to participate in this comprehensive screening program, versus 59.6% (47.2‐75.2) among those who did not ( P = .01) 8 . This approach has also been found to be cost effective among high‐risk individuals with LFS 21 …”
Section: Discussionmentioning
confidence: 99%
“…8 This approach has also been found to be cost effective among high-risk individuals with LFS. 21 Yet the data are less clear when considering WB-MRI surveillance as a solitary screening modality for individuals with cancer predisposition. A recent meta-analysis of baseline WB-MRI surveillance in 578 participants with LFS from 13 cohorts in six countries demonstrated that 225 lesions requiring clinical follow up were detected in 173 participants.…”
Section: Discussionmentioning
confidence: 99%
“…79,80 Presymptomatic cancer surveillance is cost effective for patients with germline pathogenic variants in TP53. 81 Risk-reduction surgery and intensive breast screening were cost effective in models of BRCA carrier risk management. 82 In Brazil, BRCA1/BRCA2 diagnostic and management strategies for patients with OC were considered cost effective but only when cancer-unaffected relatives of OC mutation carriers were included in the model.…”
Section: Cost-effectiveness Of Genetic Testingmentioning
confidence: 99%